2015
DOI: 10.1038/srep11269
|View full text |Cite|
|
Sign up to set email alerts
|

Nicotine absorption from electronic cigarette use: comparison between experienced consumers (vapers) and naïve users (smokers)

Abstract: Electronic cigarettes (ECs) are nicotine delivery devices that are proposed as tobacco harm reduction products to smokers. Nicotine delivery from ECs is potentially important in their efficacy as smoking substitutes. Herein, nicotine delivery from using a new-generation EC device (variable-wattage, set at 9 W) was evaluated, comparing experienced (vapers) with naïve users (smokers). Twenty-four vapers and 23 smokers participated to the study. They were asked to obtain 10 puffs in 5 minutes and then use the EC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
111
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(122 citation statements)
references
References 20 publications
7
111
1
Order By: Relevance
“…This confirms previous findings from laboratory studies showing that e-cigarettes effectively deliver nicotine to blood. 12,13 There was a slight decrease in nornicotine during e-cigarette use, which is expected as nornicotine is both a nicotine metabolite and a minor alkaloid present in tobacco, and not present in e-liquids or present in lower concentrations (relative to nicotine) than in tobacco. While we observed no significant declines in urine cotinine levels in our participants, McRobbie et al 15 noted a slight decline in cotinine levels over a period of 1 month.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This confirms previous findings from laboratory studies showing that e-cigarettes effectively deliver nicotine to blood. 12,13 There was a slight decrease in nornicotine during e-cigarette use, which is expected as nornicotine is both a nicotine metabolite and a minor alkaloid present in tobacco, and not present in e-liquids or present in lower concentrations (relative to nicotine) than in tobacco. While we observed no significant declines in urine cotinine levels in our participants, McRobbie et al 15 noted a slight decline in cotinine levels over a period of 1 month.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it remains unclear how effectively e-cigarettes deliver nicotine to the user. [8][9][10][11][12][13] Very little research on observed toxicant levels in e-cigarette users has been conducted. 14,15 To help better inform whether or not e-cigarettes pose real utility as a harm reduction device, data are needed to assess levels of nicotine, carcinogenic substances, and other toxicants in cigarette smokers who switch to e-cigarettes.…”
Section: Introductionmentioning
confidence: 99%
“…Studying E-Cig exposure is very much like trying to hit a moving target, but one where researchers are not completely sure what the target looks like, since E-Cig devices, the way that they are used, and the types/flavors of e-liquids available are constantly changing. However, some facts have been established: 1) current E-Cig devices deliver nicotine at comparable levels to cigarettes, and certainly at levels high enough to evoke physiological responses in humans and rodents (54,103,138), 2) nicotine is highly addictive and, along with its metabolites, can cause cancer and affect neuronal development in adolescents irrespective of its source (50,155), 3) e-liquids have been shown to contain potentially toxic aldehydes and ROS (146), and 4) some type of a biological response (e.g., change in cytokine levels) has been observed in the vast majority of murine in vivo and in vitro studies following E-Cig vapor/e-liquid exposure (94,133,152). Although it seems certain that E-Cig aerosols contain toxicants, it is fair to say that they likely contain less types of toxicants than cigarette smoke (i.e., E-Cig aerosols likely have hundreds of chemicals in them while tobacco smoke has thousands of chemicals).…”
Section: Effects Of E-cig Aerosols and E-liquids On Cultured Cells Frmentioning
confidence: 99%
“…Recent studies by Talih and colleagues (9) demonstrate that nicotine delivery by e-cigarettes can be modeled primarily as a concentration of nicotine concentration in the e-juice, temperature of the vaporizer, and volume of the puff. In practical terms, this means that depending on the puff volume and nicotine concentration, e-cigarettes deliver as high or higher amounts of nicotine as do conventional e-cigarettes (9,10). As e-cigarette users become more experienced, they tend to take higher-volume puffs and obtain higher levels of nicotine equaling the nicotine levels achieved by smokers of conventional cigarettes (9,10).…”
mentioning
confidence: 99%